Cervical cytology biobanking in Europe - Arbyn, Marc; Van Veen, Evert-Ben; Andersson, Kristin; Bogers, Johannes; Boulet, Gaëlle; Bergeron, Christine; Knebel Doeberitz, Magnus von; Dillner, Joakim (The international journal of biological markers, 2010)
A cervical cytology biobank (CCB) is an extension of current cytopathology laboratory practice consisting in the systematic storage of Pap smears or liquid-based cytology samples from women participating in cervical cancer screening with the explicit purpose to facilitate future scientific research and quality audit of preventive services. A CCB should use an internationally agreed uniform cytology terminology, be integrated in a national or regional screening registry, and be linked to other registries (histology, cancer, vaccination). Legal and ethical principles concerning personal integrity and data safety must be respected strictly. Biobank-based studies require approval of ethical review boards.A CCB is an almost inexhaustible resource for fundamental and applied biological research. In particular, it can contribute to answering questions on the natural history of HPV infection and HPV-induced lesions and cancers, screening effectiveness, exploration of new biomarkers, and surveillance of the short- and long-term effects of the introduction of HPV vaccination. To understand the limitations of CCB, more studies are needed on the quality of samples in relation to sample type, storage procedures, and duration of storage.
Gesehen am 25.11.2022